2022
DOI: 10.1289/ehp10389
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exposure Measurement Error on the Estimated Concentration–Response Relationship between Long-Term Exposure to PM2.5 and Mortality

Abstract: Background: Exposure measurement error is a central concern in air pollution epidemiology. Given that studies have been using ambient air pollution predictions as proxy exposure measures, the potential impact of exposure error on health effect estimates needs to be comprehensively assessed. Objectives: We aimed to generate wide-ranging scenarios to assess direction and magnitude of bias caused by exposure errors under plausible concentration–response relationships betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“… 8 The bias in the effect estimates associated with variance ratios farther from 1, and the associated correlations, in these prior studies were much larger than that found by Wei et al. 1 It can also be observed that investigating short-term exposures, where the observed correlations are higher, variance ratios are rarely found, thus the upward bias is only rarely observed. It should be noted that the ME problem gains further complexity in studies of multi-exposures.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“… 8 The bias in the effect estimates associated with variance ratios farther from 1, and the associated correlations, in these prior studies were much larger than that found by Wei et al. 1 It can also be observed that investigating short-term exposures, where the observed correlations are higher, variance ratios are rarely found, thus the upward bias is only rarely observed. It should be noted that the ME problem gains further complexity in studies of multi-exposures.…”
mentioning
confidence: 64%
“…We would like to note that some aspects of the paper by Wei et al. 1 are unique and not common in many situations and lead to a smaller reported magnitude of bias, as described below.…”
mentioning
confidence: 98%
See 3 more Smart Citations